Impact of Child Sexual Abuse on Educational Pathways of Children in Sri Lankan Tea Plantations - N. M. P. K. Kumari; L. N. P. Wedikandage (Eduscape : Journal of Education Insight, 2026)
Child sexual abuse (CSA) and its secondary consequences significantly threaten educational participation in Sri Lanka’s plantation sector. This research explores how these risks disrupt the education of children in marginalized communities, specifically focusing on the "identification-intervention gap" where institutional detection fails to provide sustained academic support. Using an institutional documentary research method, a review of records from the Kalawana Police Women and Child Protection Unit revealed that 99.9% of all formal child abuse and physical maltreatment complaints in the region originate from tea plantation environments. While general CSA data exist this article provides a context specific analysis of the identification intervention gap where institutional detection of abuse does not translate to sustained academic support leading to permanent school dropouts. In-depth interviews were conducted with five key participants, including child protection officers and experienced teachers. The interviews assisted in understanding the professional perspective regarding the gap between the identification of child abuse and the provision of effective long-term support for the child’s educational recovery. Data were analyzed thematically. The findings focus on adolescent girls (ages 13–16) in the Kalawana plantation sector who, following the detection of abuse, faced critical disruptions during their secondary schooling years. The study concludes that legal protection methods are insufficient if they do not include academic stabilization. It recommends that plantation sector schools should change their approach to better recognize and respond to students’ experiences of trauma by prioritizing emotional safety, understanding behavioral changes and adapting teaching practices to support healing as well as learning.